High turnover for ambulatory orthopedic surgery. Issue 5 (October 2021) - Shariat, Ali; Marcus, Berend; Latmore, Malikah
Abstract : Purpose of review: The trend in the perioperative management of patients having orthopedic surgery in the ambulatory setting emphasizes time-efficiency and rapid turnovers. Anesthetic techniques and management continue to evolve to increase efficiency and decrease time spent in recovery. Recent findings: Minimizing time patients spend in phase 1 recovery or bypassing phase 1 altogether, known as fast-tracking, has become an important goal in containing costs in high turnover, ambulatory settings. Anesthetic techniques, particularly implementation of regional anesthesia and multimodal analgesia, have evolved to maximize efficiency. Summary: Anesthetic goals in the setting of high-turnover orthopedic surgery include effective multimodal analgesia, decreasing monotherapy with opioids, and patient education. Regional anesthesia as part of a multimodal analgesic regimen is increasingly used in ambulatory surgery fast-tracking protocols.